2016
DOI: 10.1038/aps.2016.70
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Metrnl released into the gut lumen acts as a local regulator for gut antimicrobial peptides

Abstract: Aim: Metrnl is a novel secreted protein, but its physiological roles remain elusive. In this study, we investigated the tissue expression pattern of Metrnl in humans and explored its possible physiological role in the tissues with most highly expressed levels. Methods: A human tissue microarray containing 19 types of tissues from 69 donors was used to examine the tissue expression pattern of Metrnl, and the expression pattern was further verified in fresh human and mouse tissues. Intestinal epithelial cell-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 31 publications
(51 reference statements)
1
32
0
Order By: Relevance
“…[1][2][3][4] Metrnl gene is located on human chromosome 17q25.3 and the protein is predicted to contain 311 amino acids, with a signal peptide of 45 amino acids and without any transmembrane region, suggesting a mature protein of 266 amino acids (~30 kDa) when secreted. 1) First described in 2012, 2) Metrnl is soon being recognized as serving important roles in neural development, 2,5) white adipose browning 6) and insulin sensitization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Metrnl gene is located on human chromosome 17q25.3 and the protein is predicted to contain 311 amino acids, with a signal peptide of 45 amino acids and without any transmembrane region, suggesting a mature protein of 266 amino acids (~30 kDa) when secreted. 1) First described in 2012, 2) Metrnl is soon being recognized as serving important roles in neural development, 2,5) white adipose browning 6) and insulin sensitization.…”
mentioning
confidence: 99%
“…1) First described in 2012, 2) Metrnl is soon being recognized as serving important roles in neural development, 2,5) white adipose browning 6) and insulin sensitization. 7) Besides, it might be involved in both innate and acquired immune response, 8) in maintaining gut antimicrobial peptides 4) as well as in osteoblast function. 9) Our previous studies showed that Metrnl is highly expressed in white adipose tissue in both rodents and humans and plays important roles in adipose biology.…”
mentioning
confidence: 99%
“…Li et al demonstrated that, Metrnl is highly expressed in the gastrointestinal tract of normal donors as well as mice. On the other hand, they produced intestinal epithelial cell-speci c knockout mice, which showed no signi cant serum reduction, despite the reduction of Metrnl expression in the gastrointestinal tract [16]. A recent study performed by Zuo et al reported that Metrnl expression is higher in mesenteric adipose tissue (MAT) of the CD patients compared to the controls.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Metrnl is expressed in other tissues including muscle, liver, heart, spleen, and central nervous system (CNS). Moreover, the activated macrophages produced Metrnl, which by this fact, Metrnl may connected to the in ammatory disorders such as IBD [16]. A few studies have been done on tissue Metrnl levels in IBD disease.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the activated macrophages produced Metrnl, which by this fact, it may be connected to the in ammatory disorders such as IBD [16]. A few studies have been conducted on tissue Metrnl levels in IBD disease.…”
Section: Introductionmentioning
confidence: 99%